Assessment of the compliance with minimum quality standards by public primary healthcare facilities in Nigeria - Sidney Sampson; Laila Umar; Chisom Obi-Jeff; Folake Oni; Oluwafisayo Ayodeji; Hilda Ebinim; Ejemai Eboreime; Oluomachukwu Omeje; Otobo Ujah; Toluwani Oluwatola; Faisal Shuaib; Olugbemisola Samuel; et al. (BMC, 2024)
Abstract Achieving universal health coverage (UHC) and the Sustainable Development Goals (SDG) by 2030 relies on the delivery of quality healthcare services through effective primary healthcare (PHC) systems. This necessitates robust infrastructure, adequately skilled health workers and the availability of essential medicines and commodities. Despite the critical role of minimum standards in benchmarking PHC quality, no global consensus on these standards exists. Nigeria has established minimum standards to enhance healthcare accessibility and quality, including the Revised Ward Health System Strategy (RWHSS) by the National Primary Health Care Development Agency (NPHCDA). This paper outlines the evolution of PHC minimum standards in Nigeria, evaluates compliance with RWHSS standards across all public PHC facilities, and examines the implications for ongoing PHC revitalization efforts. The study used a cross-sectional descriptive design to assess compliance across 25 736 public PHC facilities in Nigeria. Data collection involved a national survey using a standardized assessment tool focussing on infrastructure, staffing, essential medicines and service delivery. Compliance with RWHSS minimum standards was found to be below 50% across all facilities, with median compliance scores of 40.7%. Outreach posts had a median compliance of 32.6%, level 1 facilities 31.5% and level 2+ facilities 50.9%. Key findings revealed major gaps in health infrastructure, human resources and availability of essential medicines and equipment. Compliance varied regionally, with the North-west showing the highest number of facilities but varied performance across standards. The lessons learned underscore the urgent need for targeted interventions and resource allocation to address the identified deficiencies. This study highlights the critical need for regular, comprehensive compliance assessments to guide policy-makers in identifying gaps and strengthening PHC systems in Nigeria. Recommendations include enhancing monitoring mechanisms, improving resource distribution and focussing on infrastructure and human resource development to meet UHC and SDG targets. Addressing these gaps is essential for advancing Nigeria's healthcare system and ensuring equitable, quality care for all.